Analisis pengaruh investasi industri sektor primer, sektor sekunder dan sektor tersier terhadap pertumbuhan ekonomi di Provinsi Jambi - Nurhayani Nurhayani (Jurnal Paradigma Ekonomika, 2019)
The aims of this research are to determine the economic growth in Jambi Province and the factors that influence it. The variables of this research are economic growth, investment, primary industry sector investment, secondary industry sector investment, and tertiary industry sector investment as research variables. The research model is multiple linear analysis to determine the effect of primary, secondary and tertiary sector industry investment on economic growth in Jambi Province. Based on the regression result, only the research variable of realization of primary industry sector investment, which significantly influences economic growth in Jambi Province. While investment in secondary and tertiary industry sectors did not significantly affect economic growth in Jambi Province.